NATIONAL IDENTITY AND POLITICAL PARTIES OF BOSNIAKS IN BOSNIA AND HERZEGOVINA - Mijatović, Marko (Political Review, 2024)
This paper examines the issue of the modern political tradition and national identity of Bosniaks in Bosnia and Herzegovina, the beginnings of which are linked to the period of the Austro-Hungarian occupation in 1878–1918. Starting from that time until modern political conditions, in one long period, periods of their political divisions (the Austro-Hungarian period) and exclusive attachment to certain political movements (the period of the first Yugoslavia) alternated. The decades-long dominance of the communist party (in the second Yugoslavia), This paper examines the issue of national identity and the modern political tradition of Bosniaks in Bosnia and Herzegovina, the beginnings of which are linked to the period of the Austro-Hungarian occupation in 1878–1918. Starting from that time until modern political conditions, in one long period, periods of their political divisions (the Austro-Hungarian period) and exclusive attachment to certain political movements (the period of the first Yugoslavia) alternated. The decades-long dominance of the communist party (in the second Yugoslavia), followed by the re-establishment of a pluralistic political life, is also characteristic and followed with the re-establishment of a pluralistic political life. In this paper, we want to make a synthesis of the development of the Bosniak national idea and its formation and rounding that took place in socialist Yugoslavia, especially during the civil war in Bosnia and Herzegovina from 1992 to 1995, which was closely related to their predominant political parties.